2023
DOI: 10.1021/acs.est.3c02161
|View full text |Cite
|
Sign up to set email alerts
|

River Basin Simulations Reveal Wide-Ranging Wetland-Mediated Nitrate Reductions

Abstract: River basin-scale wetland restoration and creation is a primary management option for mitigating nitrogen-based water quality challenges. However, the magnitude of nitrogen reduction that will result from adding wetlands across large river basins is uncertain, partly because the areal extent, location, and physical and functional characteristics of the wetlands are unknown. We simulated over 3600 wetland restoration scenarios across the ∼450,000 km 2 Upper Mississippi River Basin (UMRB) depicting varied assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…9 The ecological and environmental benefits offered by riverine wetlands have been extensively documented, 6 sparking global interest in constructing more of these wetlands to achieve water quality and ecological objectives at reach or watershed scales. 6,10,11 While many studies have shown the effectiveness of constructed wetlands in purifying water quality during their operational phase, 3,11 there is a scarcity of research on the environmental consequences once they are no longer in operation. Constructed wetlands, like their natural counterparts, are prone to damage from disasters and/or recession in their ecological functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The ecological and environmental benefits offered by riverine wetlands have been extensively documented, 6 sparking global interest in constructing more of these wetlands to achieve water quality and ecological objectives at reach or watershed scales. 6,10,11 While many studies have shown the effectiveness of constructed wetlands in purifying water quality during their operational phase, 3,11 there is a scarcity of research on the environmental consequences once they are no longer in operation. Constructed wetlands, like their natural counterparts, are prone to damage from disasters and/or recession in their ecological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Constructing riverine wetlands often involves modifying riverine geomorphology, especially in flashy headwater rivers where benthic and hydrological conditions are unfavorable for vegetation growth . The ecological and environmental benefits offered by riverine wetlands have been extensively documented, sparking global interest in constructing more of these wetlands to achieve water quality and ecological objectives at reach or watershed scales. ,, …”
Section: Introductionmentioning
confidence: 99%